Mineragraphic influence on the recovery of gold in the metallurgical processes of Minera Qero's Gold de Paubustamantecartambo- Cusco - Soto Mayorga, Alvaro Fernando (2020)
Mineragraphic studies allowed selecting the most suitable metallurgical process for optimal gold recovery, whose characterization both microscopic and macroscopic, allowed to undergo metallurgical tests on grinding, bottle cyanidation, centrifugal concentration, rougher flotation. As a result of these metallurgical tests on the base mineral, it allowed a 94.48% recovery in selective flotation with a blending of 36% Inkaracay vein and 64% Mina Sanca 2 vein.